Assessment of the Technological University of the Philippines-Taguig Research Division - Decapia, Rexmelle F. Jr.; Posada, Roger (Quezon City University of the Philippines Diliman, 2011)
The study was conducted to contribute to the review of the design and definition of the mission of the Technological University of the Philippines Taguig. It also aimed to formulate its vision, the priorities for its strategic policy; assist in the more efficient distribution of its resources; enhance its quality, improve its performance and fulfill its goals as defined in a contract programs or pre-established strategic plan. This assessment includes the degree to which the goals are fulfilled, an examination of scientific production and the impact of the activities carried out expressed in the form of targets achieved. Examples are the number of publications, the number of theses defended, the number of patents obtained, the institute's academic reputation and recognition at the international level, and the institute's influence on other institutions, among others. Further, the study determined the institute's prospective capability or potential, with consideration being given to the context and the opportunities available to the university for its development. Examples of this type of assessment include the analysis of developments achieved in a particular field or discipline, the analysis of the staff's research qualifications (capabilities, experience, adaptability, etc.), technological capability (access to instrumentation, etc.), economic and administrative organization (adaptability, level of bureaucracy, etc.), as well as the analysis of structural factors that facilitate or hinder the institute's activities.
This normally focuses on examining the institute's mission and vision as these determine its lines of action. It includes the analysis of aspects such as the purpose of research that is carried out and its diffusion and relevance in relation to the existing culture. Other elements of scientific activity are analyzed together with these aspects, including staff training, the publicizing of scientific developments, technology transfer, research assessment protocols, incentives and privileges as means of motivation to the faculty, etc.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Continuing education centers; Technological University of the Philippines-Taguig Research Division; Research qualification